Quantitative assessment of informative immunophenotypic markers increases the diagnostic value of immunophenotyping in mature CD5-positive B-cell neoplasms - Starostka, David; Kriegova, Eva; Kudelka, Milos; Mikula, Peter; Zehnalova, Sarka; Radvansky, Martin; Papajik, Tomas; Kolacek, David; Chasakova, Katerina; Talianova, Hana (Cytometry. Part B, Clinical cytometry, 2018)
BACKGROUND: The data on the clinical utility of the quantitative assessment of immunophenotypes in distinguishing mature CD5-positive B-cell neoplasms is limited. The study aim was to assess the diagnostic value of the quantitative assessment of a panel of 18 markers and to identify the most informative ones. METHODS: The immunophenotype of the neoplastic population was determined in diagnostic specimens from 188 patients. BD FACSCanto II flow cytometer and FACSDiva software were used to analyze the positivity/negativity and mean fluorescence intensity (MFI) of the surface expression of 18 markers. Advanced data mining methods were used to define the key differential diagnostic features of CLL/SLL (chronic lymphocytic leukemia/small lymphocytic lymphoma), MCL (mantle cell lymphoma), and CD5+ MZL (marginal zone lymphoma). RESULTS: The most informative markers for the distinction of CLL/SLL, MCL, CD5+ MZL, including atypical cases, were the MFI values of CD79b, CD20, CD23, CD43, CD38, CD11c, FMC7, CD200, kappa light chain, and their combinations. CD23 and CD200 were the most discriminant between CLL/SLL and MCL and CD23 plus CD79b between CLL/SLL and CD5+ MZL. The quantitative analysis of the most informative markers failed to accurately distinguish MCL and CD5+ MZL. The study highlights the data mining methods for the analysis and selection of the most informative immunophenotypic markers and for the design of a predictive model (diagnostic classifier), minimizing the subjectivity of expert-based assessment. CONCLUSIONS: Our data confirmed that the quantification of the expression of informative markers increases the diagnostic value of immunophenotyping in mature CD5+ B-cell neoplasms. © 2017 International Clinical Cytometry Society.
Keywords: leukemie B-buněčná; B-cells; Humans; lidé středního věku; Biomarkers, Tumor; CD5 Antigens; Lymphoma, B-Cell; lymphoma; Female; Aged; Leukemia, B-Cell; dospělí; imunofenotypizace; senioři; lidé; immunophenotyping; leukemia; nádorové biomarkery; Adult; Immunophenotyping; ženské pohlaví; Male; Flow Cytometry; Middle Aged; flow cytometry; B-buněčný lymfom; antigeny CD5; Aged, 80 and over; senioři nad 80 let; průtoková cytometrie; mužské pohlaví